The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1038/bjc.1992.252
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 receptors in human breast tumour: Localisation and quantification by histo-autoradiographic analysis

Abstract: To assess the precise role of IGF1 in benign and malignant breast diseases, we analysed the tissular localisation, characterised, and quantified specific insulin-like growth factor 1 (IGF1) binding sites in these heterogenous tissues, using histo-autoradiographic analysis (HAA). The 125I-IGF1 binding was performed on frozen tissue sections and analysed using 3H Ultrofilm autoradiography coupled to computerised image analysis. Competitive binding experiments using unlabelled IGF1, IGF2 and insulin showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In the present study, we have not quantified the changes in cell surface IGFR-I concentrations. However, using ['25I]IGF-I hisoautoradiography (Jammes et al, 1992), we confirmed that the IGFR-I is expressed solely on the epithelial component of xenografted normal human breast tissue (data not shown). Although the IGFR-I mRNA levels measured by RT-PCR could be affected by changes in the ratio of epithelial to stromal cells in the xenografts, no change to this ratio in response to ovarian steroid administration was observed as assessed by histological examination of the xenografts (Laidlaw et al, 1995).…”
Section: B4-fl and 36b4-r1 Respectively (See Materials And Methods)supporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, we have not quantified the changes in cell surface IGFR-I concentrations. However, using ['25I]IGF-I hisoautoradiography (Jammes et al, 1992), we confirmed that the IGFR-I is expressed solely on the epithelial component of xenografted normal human breast tissue (data not shown). Although the IGFR-I mRNA levels measured by RT-PCR could be affected by changes in the ratio of epithelial to stromal cells in the xenografts, no change to this ratio in response to ovarian steroid administration was observed as assessed by histological examination of the xenografts (Laidlaw et al, 1995).…”
Section: B4-fl and 36b4-r1 Respectively (See Materials And Methods)supporting
confidence: 60%
“…In both normal and malignant human breast tissue, IGF-I and IGF-II mRNA are expressed by stromal fibroblasts, but generally not by the epithelium (Yee et al, 1989;Paik, 1992), whereas the expression of the IGFR-I is restricted to epithelial cells (Jammes et al, 1992). In vitro studies of the breast cancer cells have demonstrated that the IGFs are potent mitogens (Karey and Sirbasku, 1988), and that their growth-stimulatory effects can be blocked, both in vitro and in vivo, by a specific antibody (oIR-3) to the IGFR-I (Arteaga et al, 1989;Cullen et al, 1990).…”
mentioning
confidence: 99%
“…6 Several studies have reported that IGF-IR levels are significantly higher in breast cancer tissue compared with normal breast tissue or benign tumors. [7][8][9] Patients with tumors containing a high IGF-IR gene copy number tend to have a shorter median overall survival than patients with tumors having a low amplified IGF-IR gene copy number. 10 Indeed, a recent study has shown that IGF-IR expression was 14-fold higher and that IGF-IR autophosphorylation and kinase activity were 2-to 4-fold higher in malignant breast tissue than in normal breast tissue.…”
mentioning
confidence: 99%
“…Most of the actions of IGFI and IGFII could be mediated by the type I receptor through auto/paracrine effects [14,37]. [23] and in adult muscular tissue [33]. Frozen sections (7 11 m) were processed as previously described [20].…”
mentioning
confidence: 99%